2018
DOI: 10.1515/folmed-2017-0080
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics: Evidence of Oral Health Implications

Abstract: The prevalence of common oral diseases, such as dental caries, periodontal diseases and oral candidiasis remains high in the general population. Various preventive strategies have been proposed and included in national health programs promoting oral health. Interest in probiotics in light of oral health has gradually evolved as attractive means in prevention of oral infectious diseases. The aim of the present review is to outline the current evidence on the role of probiotic species on oral health parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 58 publications
(56 reference statements)
1
30
0
6
Order By: Relevance
“…Known mechanisms of probiotics include regulating innate and acquired immunity and releasing antioxidants and bacteriocins to restore the balance of the microbial community and the immune system [2022]. Meanwhile, it is also reported that probiotics are potentially promising treatment for oral diseases such as periodontal disease, dental caries, halitosis and oral candidiasis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Known mechanisms of probiotics include regulating innate and acquired immunity and releasing antioxidants and bacteriocins to restore the balance of the microbial community and the immune system [2022]. Meanwhile, it is also reported that probiotics are potentially promising treatment for oral diseases such as periodontal disease, dental caries, halitosis and oral candidiasis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Na última década, houve um aumento das pesquisas sobre os probióticos devido ao seu potencial efeito benéfico na saúde periodontal, por meio da formação de compostos antibacterianos, atuando como "competidores" das bactérias periodontopatogênicas pelas ligações das células epiteliais excluindo os microrganismos patogênicos, além de alterar a resposta do hospedeiro, reduzindo citocinas pró-inflamatórias (Alakomi et al, 2000;Szkaradkiewicz et al, 2014;Meurman et al, 2018). animalis subsp.…”
Section: Discussionunclassified
“…Pesquisas confirmaram o resultado positivo dos efeitos das bactérias probióticas nas infecções por vírus da diarreia, distúrbios gastrointestinais, ginecológicos, colite, infecção entérica, câncer de cólon, mucosite induzida por quimioterapia, sintomas de alergia e patologias imunológicas (Harini et al, 2010;Mahasneh et al, 2018: Messora et al, 2013Sahah et al, 2013). Resultados de estudos recentes mostraram que a terapia por meio dos probióticos pode influenciar nas funções do corpo além do intestino, como sistema respiratório e a saúde mental (Harini et al,2010;Meurman et al, 2018). Não há contraindicações absolutas aos probióticos, normalmente há pouco ou nenhum efeito adverso, sendo relatados flatulência leve a moderada e desconforto gástrico, geralmente autolimitados (Kligler & Cohrssen, 2008).…”
Section: Definição E Efeitos Dos Probióticos Na Saúdeunclassified
“…and interactions between members of these genera have long been of interest to the medical community. For example, many Lactobacillus strains and their cell-free supernatants have antimicrobial activity against Streptococcal pathogens including S. mutans (Rossoni et al 2018;Söderling, Marttinen, and Haukioja 2011;Wasfi et al 2018;Ahn et al 2018) and S. pyogenes (Saroj et al 2016) (Meurman and Stamatova 2018). With a few notable exceptions (Ahn et al 2018), the mechanisms of inhibition is not fully understood.…”
Section: Discussionmentioning
confidence: 99%